Early evaluation of response to sorafenib for hepatocellular carcinoma by duplex Doppler ultrasonography. Issue 9 (11th December 2014) - Hidaka, Hisashi; Nakazawa, Takahide; Fujii, Shigeru; Yanagihara, Michiko; Minamino, Tsutomu; Takada, Juichi; Tanaka, Yoshiaki; Okuwaki, Yusuke; Shibuya, Akitaka; Koizumi, Wasaburo
<x xml:space="preserve">Abstract</x> Aim Early evaluation of the response to sorafenib for patients with hepatocellular carcinoma (HCC) remains unclear. This prospective study investigated the early evaluation of the efficacy of sorafenib in patients with advanced HCC using duplex Doppler ultrasonography (DDU). Methods Thirty‐seven Child–Pugh class‐A advanced HCC patients treated with sorafenib 400 mg b.i.d. were enrolled. Changes in portal venous area (PVA) and portal venous flow velocity (PVV) revealed by DDU before and after 2 weeks of sorafenib treatment were evaluated. The relation between the congestion index (PVA/PVV), which reflects the pathophysiological hemodynamics of the portal venous system and the tumor response, according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST), was also assessed. Results The median progression‐free survival and overall survival of all the patients was 2.8 months (95% confidence interval [CI], 2.6–3.2) and 12.8 months (95% CI, 8.7–17.0), respectively. Overall, three patients (8%) had a partial response (PR), 15 (41%) stable disease (SD) and 17 (46%) progressive disease, according to the mRECIST, and two patients (6%) could not be evaluated because of worsened conditions. The decrease in the congestion index was significantly larger in the disease control group (PR/SD) after the sorafenib treatment (P = 0.035); furthermore, the congestion index was the only significant independent predictor of disease control (P = 0.033; hazard ratio, 8.456; 95% CI, 1.182–60.484). Conclusion A decrease in the congestion index revealed by DDU provides an early evaluation of response in patients taking sorafenib for advanced HCC.